2021
DOI: 10.1038/s41564-021-00882-3
|View full text |Cite
|
Sign up to set email alerts
|

Detection of respiratory syncytial virus defective genomes in nasal secretions is associated with distinct clinical outcomes

Abstract: The kinetics of defective viral genomes appearance during infection with RSV determines the clinical outcome of the infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
56
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(62 citation statements)
references
References 54 publications
6
56
0
Order By: Relevance
“…DVGs detected early in the course of infection were associated with mild disease, and DVGs detected later were linked to severe disease. Patients with DVGs had heightened expression of cytokines, including IFN alpha, which aligned with past studies linking induction of IFN to DVGs and DIPs [137].…”
Section: Dips and The Immune Responsesupporting
confidence: 80%
“…DVGs detected early in the course of infection were associated with mild disease, and DVGs detected later were linked to severe disease. Patients with DVGs had heightened expression of cytokines, including IFN alpha, which aligned with past studies linking induction of IFN to DVGs and DIPs [137].…”
Section: Dips and The Immune Responsesupporting
confidence: 80%
“…[ 11 ] However, clinical sequencing has revealed that they are a common component of viral infections and can be associated with disease outcome. [ 12 14 ] Their potential ability to modulate the course of disease has now sparked a renewed interest in their therapeutic potential. [ 15 18 ]…”
Section: Introductionmentioning
confidence: 99%
“…DIPs have been demonstrated in numerous contexts to interfere with wild-type (WT) virus replication (hence the name), ostensibly either by outcompeting wild-type genomes for replication and packaging and/or by triggering innate immune activation ( 3 7 ). Recent studies have correlated the abundance of DIPs within clinical samples with severity of both IAV and respiratory syncytial virus infection, suggesting a role for DIPs in modulating viral pathogenicity ( 8 , 9 ). Despite being discovered over 60 years ago, the specific molecular processes that drive DIP formation, as well as the effects of DIPs on the collective behavior and pathogenicity of viral populations, remain mysterious ( 10 , 11 ).…”
Section: Introductionmentioning
confidence: 99%